Al-Akhlóq (Ethics) Perceptions In Islam: An Interpretation Through Mawsõñah Al-Akhlóq Of Khólid Al-Kharróz - Mohammed Muneer'deen, Olodo Al-Shafi'i; Mohd Safri, Ali (2017)
Islam contains a general code of conduct; there is neither much doubt nor disagreement on this. That Islam as both a religion and way of life encompasses all religious issues and affairs affecting human‘s life is also a fact unchallenged by those of consummate mind. One important aspect of all facets of Islamic discussions, that upon which all arguments sprout and agreements are either diverged and/or reached, that which for its effectiveness also relies on intellectual foundation, is al-AkhlÉq (the Ethic). Ethic cum conduct is pertinent in Islamic SharÊÑah, Law, regulations, and legislations. Ethic could be explained in many ways and aspects, it differs from one perspective to the other, and sometimes from one individual to the other, but seldom from one religion to the other, at least this is one area this paper would like to maintain. This paper thus seeks to explore the meaning of ethics and the perceptions it has in Islam in the light of KhÉlid bin JumÑah bin ÑUthmÉn al-KharrÉz‘s MawsËÑah al-AkhlÉq. It is also the aim of the paper to expatiate the relation cum the importance of, and the roles played by, ethic in jurisdiction. The paper commonly employs qualitative library approach in collecting and analyzing the data. The paper maintains that the core values and sources of ethic and conduct is found in Islam, but unfortunately its positive employment among the Muslims might not be as encouraging and emulating.